Komunikasi Instruksional Pada Program Kesetaraan Paket C - Ari Usman; Ani Yuningsih; Ike Junita Triwardhani (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Students in the high school equivalency program have their own uniqueness including: age, marital status, and socioeconomic status. They have experienced dropout and have not carried out learning activities for a long time. During the COVID 19 pandemic, most of the learning process takes place online, which is not easy for them. The research entitled